Digital Communication Analysis on the Marketing of SME’s (Small and Medium Enterprises) by Karang Taruna of Ciampea Udik Village in the Era of Globalization - Kumara, Dedek; Wardani, Surti (Sean Institute, 2025)
The Youth Organization (Karang Taruna) of Ciampea Udik Village, as a Small and Medium Enterprises (SMEs) actor, has great potential for growth; however, they still face challenges in adopting digital technology as part of their marketing strategy. Karang Taruna in Ciampea Udik Village, as a Small and Medium Enterprises (SMEs) actor, also needs to optimize the use of digital communication to enhance marketing effectiveness and expand market reach. Digital communication encompasses various tools and platforms such as social media, websites, email marketing, and instant messaging applications that can be used to reach consumers broadly and efficiently. The use of online media as a marketing tool allows SMEs to interact directly with customers, build brand awareness, and promote products at a lower cost compared to traditional media. However, the implementation of digital communication in rural areas is often hindered by limitations in human resources, infrastructure, and access to technology.